Drug Resistance and Novel Therapeutic Approaches in Invasive Candidiasis - Murphy, Sarah E.; Bicanic, Tihana (Frontiers in Cellular and Infection Microbiology, 2021)
Candida species are the leading cause of invasive fungal infections worldwide and are associated with acute mortality rates of 50%. Mortality rates are further augmented in the context of host immunosuppression and infection with drug-resistant Candida species. In this review, we outline antifungal drugs already in clinical use for invasive candidiasis and candidaemia, their targets and mechanisms of resistance in clinically relevant Candida species, encompassing not only classical resistance, but also heteroresistance and tolerance. We describe novel antifungal agents and targets in pre-clinical and clinical development, including their spectrum of activity, antifungal target, clinical trial data and potential in treatment of drug-resistant Candida. Lastly, we discuss the use of combination therapy between conventional and repurposed agents as a potential strategy to combat the threat of emerging resistance in Candida.